Air Benzene's Concentration, Urine Trans,Trans-Muconic Acid's Concentration and Health Disturbance of X's Fuel Station Employee in South Jakarta - Diva Madya Resdwivani (JURNAL KESEHATAN LINGKUNGAN, 2018)
Benzene is an aromatic compound which is easy to evaporate that is found in fuel oil. Benzene in the air can affect to human's health if inhaled because benzene can be metabolized in the body. The aim of this research was analyze benzene's concentration in air on X's fuel station in South Jakarta, urine trans,trans-muconic acid's concentration, and health disturbance of fuel station's employee. This research was a descriptive with cross-sectional study. There were 8 respondents in this research with defined criteria. X's fuel station air benzene's concentration be measured in 3 points (2 points in filling area and 1 point in office area) on 2 different times (in the morning and in the afternoon). The result of this research, X's fuel station air benzene's concentration were 0,025–0,233 ppm and there was no air benzene's concentration more than the threshold values (0,5 ppm) in filling area or administration area. There were 3 of 8 respondents had trans,trans-muconic acid's levels that is more than 500 Î¼g/g creatinin. Health disturbance that experienced by workers were nervous system disorders (62%) and kidney disturbance (50%). Therefore, workers should use PPE such as respirator mask and company should do rotation for workers.